Walcast : sistema de mejoramiento de la comunicación de interpretación a grupos de visitantes en planes de Senderismo (2020)
Purpose - The purpose of this project began with achieving improvements in the satisfaction of visitors and tourists who consume tourist services within natural reserves of Colombia, in this case, the most characteristic service and object of study was hiking. We were located within the Farallones de Santiago de Cali National and Natural Park, in which we identify that the Trekking Plans are carried out in groups of 5 to 8 Visitors, and in the company of a Tourist Interpreter. With all this, we discovered that reserves like this completely lack elaborate infrastructure that guarantees high quality of execution of their tourist services (such as the absence of Internet connection), and it is for this reason that we decided to explore and implement technologies that facilitate the accompaniment provided by tourist interpreters (nature reserve officials), and also guarantee increases in visitor satisfaction that to date have not been achieved. Design /methodology / approach - The methodology implemented in this research project is based on the Double Rhombus Model, which is based on the principles of Design Thinking, and is divided into 4 main stages that helped define the structure and development of this project, which they are: Map, Explore, Build and Test. During the application of this methodology, we had the opportunity to visit the Farallones de Cali PNN and study in depth the execution in the field of a hiking plan, carry out group interviews and individual interventions to more than 10 Tourist Interpreters and Visitors or Tourists who have previously made Hiking. With all this we were able to Build a solution system with the supervision and evaluation of experts in Industrial Design from the Faculty of Design of the Icesi University of Santiago de Cali, and finally Test the results with Tourist Interpreters and Visitors mentioned above.